Control of postharvest fungal diseases in fruits using external application of RNAi - de Oliveira Filho, Josemar Gonçalves [UNESP]; Silva, Guilherme da Cruz; Cipriano, Lavínia; Gomes, Mariana; Egea, Mariana Buranelo (Wiley, 2021)
Abstract: Contamination with a variety of filamentous fungi can cause deterioration of food and agricultural products. Fungal contaminations reduce the quality and the shelf life of fresh fruits and are one of the main causes of economic loss in the global fresh fruit industry. Although chemical fungicides are effective and traditionally used to control postharvest fungal diseases, they are harmful to human health. In this context, use of RNA interference (RNAi)-based fungicides is a promising alternative strategy. Spray-induced gene silencing (SIGS) is an innovative RNAi-based approach for silencing target genes in phytopathogens. This review aims to discuss the recent findings on the use of RNAi-based fungicides to control the postharvest spoilage of fresh fruits. Practical Application: Control of postharvest fungal diseases is one of the most important strategies to make food available to consumers longer. In this sense, the external application of RNAi seems to be technologically advantageous and efficient as it helps to maintain the characteristics of plant products. In this sense, this review discussed what is possible to find in the literature regarding this new technology.
Keywords: fresh vegetables; gene silencing; phytopathogens; postharvest spoilage; RNAi